Functional relevance as a principle of translation problem-solving - Sang, Zhonggang (Frontiers in Psychology, 2022)
Translation is both an interpretive use of language and an activity of problem-solving. Gutt (1991; 2000; 2004; 2006) adopts a Relevance-Theoretic approach to unveil the inferential nature of translation as interpretive language use. He holds that in translating a translator aims to seek the interpretive resemblance between the source text and the target text. However, Gutt does not explain how the interpretive resemblance can be achieved when translation problems arise. Textual function refers to the intended contextual effects that a text yields on the part of the readers. Considering that it is only when the textual outcome of a translation activity is both relevant and functional that it is a successful interpretive use of language, we propose Functional Relevance as a principle of translation problem-solving. Namely, a translator needs to strategize their solutions to translation problems by making the explicatures and implicatures of the target language text resemblant enough both to justify its reader’s processing effort and to fulfill the contextualized textual functions of translation. This can be exemplified by two English translations of Chinese medicine pun poems in a pien wen, an archaic literary genre popular in China during the tenth century.